1988
DOI: 10.1128/mcb.8.2.679
|View full text |Cite
|
Sign up to set email alerts
|

The rat alpha-tropomyosin gene generates a minimum of six different mRNAs coding for striated, smooth, and nonmuscle isoforms by alternative splicing.

Abstract: Tropomyosin (TM), a ubiquitous protein, is a component of the contractile apparatus of all cells. In nonmuscle cells, it is found in stress fibers, while in sarcomeric and nonsarcomeric muscle, it is a component of the thin filament. Several different TM isoforms specific fdr nonmuscle cells and different ypes of muscle cell have been described. As for other contractile proteins, it was assumed that smooth, striated, and nonmuscle isoforms were each encoded by different sets of genes. Through the use of Si nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
144
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(149 citation statements)
references
References 46 publications
5
144
0
Order By: Relevance
“…These include the fetal isoforms ␣SkA (Acta1) and cardiac ␤MHC (Myh7), well known to be upregulated in cardiac hypertrophy, as well as myosin light chains, cardiac myosin-binding protein C, troponin C and T, and tropomyosin genes (Supplemental Table S1). The tropomyosin genes are regulated by alternative splicing in a tissue-specific manner (57), and the RAE230A array probe sets can distinguish some of the alternatively spliced isoforms. For example, probe set 1370287_a_at recognizes the smooth muscle-specific exon 9d and showed an expression level of 1,157 and induction of 1.3-fold by FN, whereas probe set 1368724_a_at recognizes the striated muscle-specific exon 9b and showed an expression level of 16,414 and induction of 2.1-fold by FN in cardiac myocytes.…”
Section: Fibronectin-induced Cardiomyocyte Hypertrophymentioning
confidence: 99%
“…These include the fetal isoforms ␣SkA (Acta1) and cardiac ␤MHC (Myh7), well known to be upregulated in cardiac hypertrophy, as well as myosin light chains, cardiac myosin-binding protein C, troponin C and T, and tropomyosin genes (Supplemental Table S1). The tropomyosin genes are regulated by alternative splicing in a tissue-specific manner (57), and the RAE230A array probe sets can distinguish some of the alternatively spliced isoforms. For example, probe set 1370287_a_at recognizes the smooth muscle-specific exon 9d and showed an expression level of 1,157 and induction of 1.3-fold by FN, whereas probe set 1368724_a_at recognizes the striated muscle-specific exon 9b and showed an expression level of 16,414 and induction of 2.1-fold by FN in cardiac myocytes.…”
Section: Fibronectin-induced Cardiomyocyte Hypertrophymentioning
confidence: 99%
“…The orientation of the clones was determined by restriction digestion with PstI and the sequence of clones in the correct orientation was confirmed. Northern-blot analysis was carried out using α-tropomyosin, SM22α and β-actin cDNA probes as described previously [12,34,35].…”
Section: Reverse-transcriptase Pcr (Rt-pcr) and Cloningmentioning
confidence: 99%
“…Whereas the smooth muscle rich tissues such as bladder and aorta showed nearly complete exon 2 inclusion and the striated muscles showed full inclusion of exon 3, a number of other tissues with little smooth muscle content, such as liver and spleen, showed significant percentages of exon 2 inclusion. Notably, these tissues had very low levels of ␣TM expression, which had not been detectable using nuclease protection or Northern blot (18). Subsequent analyses of GTM3 transgene splicing indicated that bladder and aorta provided a robust regulatory environment that was able to support significant levels of transgene exon skipping in all mouse lines, even with high levels of transgene expression.…”
Section: Figmentioning
confidence: 99%
“…This had previously been surveyed qualitatively by nuclease protection and was restricted primarily to those tissues with high levels of expression (18,19).…”
Section: Fig 2 Smooth Muscle Restricted Egfp Expression In Gtm2mentioning
confidence: 99%
See 1 more Smart Citation